Pengaruh Bimbingan Guru PAK terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas X SMK Negeri 1 Sigumpar Tahun Pembelajaran 2024/2025 - David Leo Fernando S; Nisma Simorangkir; Raikhapoor Raikhapoor; Lustani Samosir; Damayanti Nababan (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine the extent of the influence of PAK teacher guidance on the interest in learning Christian Religious Education and Character Education of class X students of SMK Negeri 1 Sigumpar in the 2024/2025 Academic Year. With the hypothesis that there is a positive influence of PAK teacher guidance on the interest in learning Christian Religious Education and Character Education of class X students of SMK Negeri 1 Sigumpar in the 2024/2025 Academic Year. Using a descriptive quantitative research method. The population of all students of class X SMK Negeri 1 Sigumpar in the 2024/2025 Academic Year who are Protestant Christians is 50 people. This study is a population study. The research instrument is a closed questionnaire. The results of data analysis obtained: a) The rcount value = 0.871 indicates a positive relationship and a very strong level of relationship in the interval 0.800 - 1.00 between PAK teacher guidance and students' interest in learning Christian Religious Education and Character Education. b) The determination test found that the influence was 75.86%. The study concluded that there was a positive influence of PAK teacher guidance on the interest in learning Christian Religious Education and Character Education of class X students of SMK Negeri 1 Sigumpar in the 2024/2025 Academic Year.